The Analysis of Floodgate Network Based on A Combination of Betweenness Centrality and Maximum Flow - เพ็งศิริ พฤฒิพงศ์; สดสี สุนันฑา; มีสัจ พยุง (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2016)
- This paper proposes an analysis of floodgate network based on a combination of Betweenness Centrality and Maximum Flow approach, which is called "BC-Max". It applies the theory of graph to measure the Betweenness Centrality (BC) on each floodgate in order to identify a route of drain water from source to sink floodgates. Herein, the BC is also used for calculating Maximum Flow values assigned as a draining water performance in each floodgate. In this work, the proposed work, BC-Max presents a route and a maximum flow of water draining by considering BC-Max value. The BC-Max of selected floodgate must be greater than an average BC value. The BC-Max is evaluated on a floodgate network of Southen Pasak Operation and Maintenance Project. The results shown that the average BC of this network was 0.043. As well as, the most important floodgate was Phra Mahindra and its BC-Max value was 0.787. Finally, efficient 9 routes of water draining were presented with an average of maximum flow value 24.333 m3/s.